2022
DOI: 10.3390/ijms23020789
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of CaCO3-Coated Vesicles by Biomineralization and Their Application as Carriers of Drug Delivery Systems

Abstract: We fabricated CaCO3-coated vesicles as drug carriers that release their cargo under a weakly acidic condition. We designed and synthesized a peptide lipid containing the Val-His-Val-Glu-Val-Ser sequence as the hydrophilic part, and with two palmitoyl groups at the N-terminal as the anchor groups of the lipid bilayer membrane. Vesicles embedded with the peptide lipids were prepared. The CaCO3 coating of the vesicle surface was performed by the mineralization induced by the embedded peptide lipid. The peptide li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Porous calcium carbonates and phosphates have demonstrated their potential as effective drug carriers due to their biocompatibility and biodegradability [238][239][240]. Miyamaru et al designed and synthesized peptide lipids with specific sequences, which were then incorporated into vesicles and mineralized to create CaCO 3 -coated vesicles [241]. The mineralized vesicles retained their spherical shape and had inner spaces for drug cargo, with the CaCO 3 shell dissolved under weakly acidic conditions, such as a pH of 6.0 to release the encapsulated drugs, making them potential candidates for cancer therapies.…”
Section: Drug Delivery Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Porous calcium carbonates and phosphates have demonstrated their potential as effective drug carriers due to their biocompatibility and biodegradability [238][239][240]. Miyamaru et al designed and synthesized peptide lipids with specific sequences, which were then incorporated into vesicles and mineralized to create CaCO 3 -coated vesicles [241]. The mineralized vesicles retained their spherical shape and had inner spaces for drug cargo, with the CaCO 3 shell dissolved under weakly acidic conditions, such as a pH of 6.0 to release the encapsulated drugs, making them potential candidates for cancer therapies.…”
Section: Drug Delivery Applicationmentioning
confidence: 99%
“…Ideally, a biomineral-based composite used in regenerative medicine should degrade at a rate that matches the rate of tissue regeneration. Biodegradability allows the release of ions or drugs such as growth factors and antibiotics that could help promote bone tissue regeneration as well [ 159 , 241 , 248 , 249 ]. However, controlling the degradation rate of these composites can be challenging.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…Moreover, S. Stojanov et al [ 4 ] reported the incorporation of vaginal lactobacilli into electrospun nanofibers to achieve a prospective solid vaginal delivery system, and further, the fluorescent proteins were incorporated to differentiate them and allow their tracking in the future probiotic-delivery investigations. C. Miyamaru et al [ 5 ] developed CaCO 3 -coated vesicles by biomineralization and further their utilization as carriers of drug-delivery systems. In this Special Issue, M.B.…”
mentioning
confidence: 99%